Empowering local businesses through Masjid-Based Economy Model - Md Sabri, Sabiroh; Shafee, Mohd Imran Khusairi; Abd Mutalib, Hasyeilla; Annuar, Nursyamilah; Sebayang, Asnita Frida; Hayati, Fitroh; Hayati, Ria (International Journal of Accounting, Finance and Business, 2025)
Historically viewed primarily as places of worship, mosques have evolved into multifunctional institutions that can facilitate entrepreneurship, community trading, and skills development. This study explores the potential of a Masjid-based economy model in empowering local businesses within the Muslim community, highlighting the unique role that mosques can play as economic hubs. It investigates various initiatives undertaken by selected mosques in Malaysia, focusing on how these religious institutions can support local business efforts through the effective use of Islamic financial principles such as zakat (charitable giving) and waqf (endowments). Employing a qualitative approach, this study includes detailed case studies that illustrate successful mosque-led initiatives aimed at promoting local entrepreneurship. By analyzing these initiatives, the study seeks to understand the impact of the Masjid-based economy model on business sustainability and community welfare. Interviews with mosque administrators, local business owners, and community members provide insights into the challenges and successes experienced in implementing these economic activities. The findings revealed that the Masjid-based economy model can play a pivotal role in strengthening local economies, particularly through collaborative efforts between religious institutions and local enterprises. The unique contribution of this study lies in its systematic exploration of how Islamic financial principles and mosque resources can be integrated to create a replicable framework for economic empowerment, offering a practical model for communities globally. This research contributes to the ongoing discourse on Islamic finance and community development, offering valuable insights into how religious institutions can be leveraged for economic growth and social betterment.